Relationship between maternal self-efficacy and functional status four months after delivery in Iranian primiparous women - Mojgan Mirghafourvand; Marzieh Bagherinia (Taylor & Francis Group, 2018)
Introduction: Postpartum women experience changes in their physiological and psychological functions as they adapt to their parenting role. The objective of this study was to examine the association between maternal self-efficacy and functional status in postpartum period. Methods: In this cross-sectional study, 305 Iranian women were selected randomly via a two-stage cluster sampling method at the end of the fourth month postpartum in 25 healthcare centers of Tabriz-Iran, 2016. Data were collected using the socio-demographic characteristics questionnaire, self-efficacy scale and inventory of functional status after childbirth. The statistical tests including Pearson correlation, Independent sample t-test, one-way ANOVA and General linear model were used for data analysis. Results: A significant positive relationship was observed between functional status and self-efficacy (p < 0.001, r = 0.359). According to the adjusted general linear model, self-efficacy, mother's age, income status and planned pregnancy have statistically significant relationships with functional status and explain 33.5% of the variance in the functional status score. Conclusion: The findings of the present study showed that increased postpartum maternal self-efficacy is associated with improved functional status, which requires health providers to evaluate postpartum maternal self-efficacy and make the necessary interventions if it is low.